Body image, aging, and identity in women over 50: The Gender and Body Image (GABI) study. (2nd January 2017) - Hofmeier, Sara M.; Runfola, Cristin D.; Sala, Margarita; Gagne, Danielle A.; Brownley, Kimberly A.; Bulik, Cynthia M.
ABSTRACT: We conducted a qualitative study of 1, 849 women over age 50 to capture the thoughts, feelings, and attitudes that women at middle age have about their bodies and the experience of aging. Via an open-ended question online survey, four primary themes emerged: (a) the physical and psychological experience of aging; (b) the injustices, inequities, and challenges of aging; (c) the importance of self-care; and (d) a plea for recognition of the need to maintain a contributory role in society. Results highlight the complexities of women's psychological and physical aspects of aging and point toward important topics worthy of further study in this growing population.